The Long-Term Impact of Maternal Anxiety and Depression Postpartum and in Early Childhood on Child and Paternal Mental Health at 11–12 Years Follow-Up - Walker, Annika L.; Peters, Priya H.; de Rooij, Susanne R.; Henrichs, Jens; Witteveen, Anke B.; Verhoeven, Corine J. M.; Vrijkotte, Tanja G. M.; de Jonge, Ank (Frontiers in Psychiatry, 2020)
Background: Postpartum maternal anxiety and depression can affect child development and family functioning. However, the long-term impact of postpartum maternal anxiety and depression on child and paternal mental health is understudied. The present large-scale prospective cohort study is one of the first to investigate whether maternal anxiety and depressive symptoms postpartum and at child age 5-6 years separately and synergistically increase paternal anxiety and depressive symptoms and child emotional problems in early adolescence at age 11-12 years. Secondly, we investigated whether concurrent paternal anxiety and depressive symptoms at child age 11-12 years moderated the association between maternal anxiety and depressive symptoms in the postpartum period and at child age 5-6 years with child emotional problems at age 11-12 years. Methods: This study is part of the Amsterdam Born Children and Development (ABCD) cohort study, the Netherlands (N = 2.298). Maternal postpartum anxiety and depressive symptoms were assessed using the State-Trait Anxiety Inventory (STAI) and the Center for Epidemiologic Studies Depression Scale (CES-D) at 13 weeks postpartum. Maternal anxiety and depressive symptoms at child age 5-6 years and parental anxiety and depressive symptoms at 11-12 years were assessed using the Depression Anxiety Stress Scale (DASS-21). Child emotional problems were reported by the child and a teacher using the Strengths and Difficulties Questionnaire (SDQ). Multivariable linear regression was conducted, adjusted for demographic, perinatal/obstetric confounders and affective symptoms of the other family members at 11-12 years. Results: Neither maternal anxiety nor depressive symptoms were related to paternal depressive symptoms at child age 11-12 years, while maternal postpartum depressive symptoms, depressive symptoms at 5-6 years and maternal anxiety at 5-6 years were positively related to paternal anxiety at 11-12 years. However, effect sizes were small. Only maternal postpartum depression was positively but weakly associated with more child emotional problems at 11-12 years. Although paternal concurrent affective symptoms were positively related to more child emotional problems in early adolescence, they did not moderate the association between maternal symptoms and child emotional problems. Conclusions: Our results indicate that fathers and children seem to be affected only to a small extent by maternal postpartum anxiety or depression.